Low energy fragments from O2+ + H2 collisions following single and double electron removal from the target. Issue 16 (January 2020) - Juhász, Z; Vizcaino, V; Chesnel, J-Y; Kovács, STS; Herczku, P; Demes, S; Rácz, R; Biri, S; Sulik, B
Synopsis: Fragmentation of H2 by 20-keV O 2+ was studied. A time of flight setup was developed to measure the low-energy fragment ions originating from singly ionized target molecules. High-energy fragments stemming from double electron removal were measured by an electrostatic spectrometer. The contribution of the low-energy fragments is significant but smaller than that of the energetic ones. Though single electron removal is more probable it less likely leads to dissociation. A statistical type model shows a good agreement with the experimental results.